The Assessment of Immunomolecular expression and prognostic role of TLR7 among patients with Prostatitis - AlSaimary, Ihsan Edan; Aldhaheri, Hussein Naeem; ALMusafer, Murtadha Mohammed (Jour Med Resh and Health Sci, 2020)
The Aim of this study was to determine Immunogenetic expression of Toll-like receptor gene clusters related to prostatitis, to give acknowledge about Role of TLR in prostatitis immunity in men. A case–control study included 135 confirmed prostatitis patients And 50 persons as a control group. Data about age, marital status, working, infertility, family history and personal information like (Infection, Allergy, Steroid therapy, Residency, Smoking, Alcohol Drinking, Blood group, Body max index (BMI) and the clinical finding for all patients of Prostatitis were collected , The molecular expression study include extracting DNA from blood of Prostatitis patients , Prostitis patients and Control group by using specific primers for conventional PCR and Real Time PCR , the amplification of all extracted DNA from blood samples was preform and confirm by using electrophoresis with (100volt/30min). PCR product was 149bp for TLR7 on agarose gel (1%), (50voltage for 1hour) with a presence 100%. The results of the present study indicate that the Toll like receptor alleles associated with risk of prostatitis.